The Urgency of Land Bank: Maintaining The Existence of Land Acquisition For Development - NUGROHO, Sigit Sapto (Protection: Journal Of Land And Environmental Law, 2024)
This study aims to analyze the urgency of land bank in maintaining the existence of land acquisition for development. This research method uses a normative legal research method with a statutory approach and a conceptual approach. The types and sources of legal materials used are primary, secondary and non-legal materials. The method of collecting legal materials uses the literature study method. Analysis of legal materials using qualitative descriptive analysis. Based on the research results show that the urgency of the Land Bank in Land Procurement activities for development has a function to overcome the problem of the form and value of compensation for land acquisition objects, prevent the growth of an inventory of land needs for development activities for the public interest and reduce land acquisition activities that require large costs and which take rights.